Analisis Integratif Kinerja Keuangan dan Implementasi Green Accounting dalam Memprediksi Nilai Perusahaan - Ali Jamaludin; Arini Eka Syahrani; Deni Saeful Rizal; Yulianto Hadi (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
This study aims to analyze the impact of financial performance—measured by total asset turnover, return on assets, and the debt-to-equity ratio—and the implementation of green accounting on the firm value of food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This quantitative study involved a population of 95 companies, with a sample of 20 companies selected using purposive sampling. Secondary data were obtained from the Indonesia Stock Exchange website and the official websites of the respective companies. Data analysis was conducted using panel multiple regression with Eviews 13 software. The results indicate that total asset turnover has no effect on firm value, whereas return on assets, the debt-to-equity ratio, and green accounting have a positive effect on firm value. Collectively, these four variables have a significant positive effect on firm value. The practical implication of this study is that investors should comprehensively consider various aspects—particularly ROA, DER, and corporate commitment to the environment (green accounting)—as indicators of a company's performance and future prospects.